REPRESENTAÇÕES SOCIOCULTURAIS NO LIVRO DIDÁTICO DE PLE - Sebbagh, Heloisa Scalise Taques Fonseca (2016)
Our search analyze the activities proposed by three Portuguese foreign language textbooks with the purpose to verify their respective theoretical approach proposals, as well as their vision of the inherent world, on which they define their subject matters, didactic-methodological and discursive. Our main objective was to evaluate the possibility to consider these handiworks a source of resources for teachers of Portuguese language to foreigners, who seek to build a knowledge through intercultural perspective. In consequence, we studied authentic and constructive texts, pictures, photos and any other proposed activities, as socio-cultural representation, to evaluate the language and culture concepts of these textbooks. Thus, we intend to highlight if the didactic handiworks analyzed can work as true cultural mediators. We based our search on the language concept developed by the Bakhtin Circle, which supports the vision of multi-discursive and dialectic culture being in constant evolution, recognized by several authors, like Terry Eagleton (2011), Homi Bhabha (1998) and Henrique Jansen (2002;2005; 2007; 2012). We started from the intercultural perspective, which considers a foreign or second language teaching and learning approach not only as a domain of language code, but also as a dialogue between individuals, who now take their distance, now approximate themselves, creating a third space without defined boundaries, where the cultural identities are (un)built. We observe that the textbooks analyzed stay on a perspective of monological lecture,which shows a general representation of the other and characterize a traditional vision of culture. Moreover, when revealing only the voices of their own authors, the handiworks discriminate the intercultural dialogue and limit the learning process to replicate the vision and interpretation of their authors. Consequently, the textbooks do not act as cultural mediators, delegating then to the teachers the responsibility to complement them, case they expect to use them as auxiliary resource following an intercultural perspective.